DIGITAL LITERACY TRAINING FOR PRE-SCHOOL TEACHERS IN THE ERA OF INDUSTRIAL REVOLUTION 4.0: PELATIHAN LITERASI DIGITAL GURU PAUD DI ERA REVOLUSI INDUSTRI 4.0 - Nuroh, Ermawati Zulikhatin; Liansari, Vevy (Antis-publisher, 2024)
The purpose of this training is to achieve the following objectives; 1) Share information on government literacy initiatives. 2) Assist teachers in finding affordable and reliable sources for textbooks through literacycloud.org. 3) Support teachers in conducting research that can be published in journals. 4) Fulfilling the community service obligation of an institution. This training took place at TK ABA 3 Randegan in Tanggulangin Sidoarjo. It involved 18 teachers and the principal. The training used methods of lecture, question and answer, practicum, discussion using applications and online article searches. The trainees used their cell phones and leptops. The team responsible for implementing the program determined that the digital literacy training went according to plan and achieved its goal of improving participants' digital literacy skills.